Karst thermal reservoir tracer test and seepage characteristics analysis in Niutuozhen geothermal field in Xiong’an New Area - Qiao, Yong; Li, Shaohua; Yan, Kangnan; Zuo, Yinhui; Zhang, Tao; Tian, Lanxi; Sun, Yigao (Frontiers in Earth Science, 2023)
The carbonate rock karst thermal reservoir in the Niutuozhen geothermal field is a high-quality geothermal resource with significant development potential. However, due to the strong heterogeneity of karst thermal reservoirs, the connectivity between recharge and production wells is hard to determine, which seriously restricts the sustainable development of the Niutuozhen geothermal field. Therefore, this study revealed the hydraulic connection between the recharge and production well through the tracer test, quantitatively characterized the seepage characteristics of the reservoir combined with the numerical simulation, and proposed the deployment of the recharge well. The results show that the total recovery rate of the tracer is 0.42%, indicating that there are a small number of communication channels with a good hydraulic connection between the recharge and production well in the experimental area, and the recharge will not cause thermal breakthrough within a short time period. The velocity of recharge water can reach 359 m/d at the fastest, and the directions of dominant channels are concentrated in the NW, N, and E directions centered on the recharge well, this is consistent with the characteristics of regional fractures, recharge wells should be avoided deployed in those directions. The results provide effective information for the prediction of the thermal breakthrough time and the accurate establishment of the thermal reservoir model in the Niutuozhen geothermal field and also provide a scientific basis for the sustainable utilization of the carbonate karst thermal reservoir geothermal resources.